PEMIKIRAN KRITIS IBNU CHAZM AL-ANDALUSY TENTANG KONSEP CINTA DALAM TEKS THAUQUL-CHAMÄMAH FIL-ILFAH WAL-ULLÄF - Farhah, Eva; Muslifah, Siti; Ahmadi, Rizqa (ATAVISME, 2014)
The research adopts the genetic structuralism theory with its emphasis on literary text (intrinsic analysis), socio-cultural background (historic social reality observation), and the writer. The method is the dialectic method, mutual relations between structures of a literary work (the intrinsic features of ?Thauqul-Cham?mah fil-Ilfah wal-Ull?f?), historic materialism (socio-cultural background of Andalusia at the time the work was written), and the writer of ?Thauqul-Cham?mah fil-Ilfah wal-Ull?f?. The conclusion of the research is that according to Ibnu Chazm Al-Andalusia, the concept of love (Al-chubbun-nazhary) must be based on syari?ah. In another word, the theory of love, the cause of love, expressing love, maintaining love, meeting and ?leaving? the one, must be based on syari?ah. Key Words: genetic structuralism; Thauqul-Cham?mah fil-Ilfah wal-Ull?f; dialectic method;, vision (intellectual thought); concept of love Abstrak: Penelitian ini memanfaatkan teori strukturalisme genetik untuk mengungkapkan unsur intrinsik (struktur teks) berdasarkan yang terdapat dalam teks, latar belakang sosial (sosial kultural), dan penulisnya. Metode yang digunakan adalah metode dialektik yang bekerja dengan bermula dari teks dan berakhir kepada teks ?Thauqul-Cham?mah fil?Ilfah wal-Ull?f?. Hasil analisis penelitian terkait konsep cinta (Al-chubbun-nazhary) yang berupa pemikiran kritis Ibnu Chazm Al-Andalusy adalah konsep cinta yang sesuai syariat. Dengan kata lain, konsep cinta, penyebab orang jatuh cinta, perilaku atau ekspresi orang yang jatuh cinta, menjaga kesucian cinta, pertemuan dan perpisahan, kesemuanya berdasarkan syariat.